2020
DOI: 10.1021/acs.est.0c05355
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Model to Decipher Relationships among Water, Sanitation, and Health in Colonias-Type Unincorporated Communities

Abstract: The colonias along the United StatesMexico border are generally self-built neighborhoods of low-income families that lack basic infrastructure. While some government assistance has provided roads and electricity, water and wastewater services are still lacking in many colonias. This research is the first to collect a comprehensive dataset on water, sanitation, health, and living conditions in these unincorporated neighborhoods through collection of water samples and surveys; 114 households in 23 colonias acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
(127 reference statements)
0
17
0
Order By: Relevance
“…Most studies either focused on one or the other, with some studies only examining measured water quality using quantitative methodologies, and other studies only discussing perceived water quality using more qualitative methodologies (e.g., Moya 2017). However, Rowles et al (2020a) found that the relationships between perceived and measured water quality suggest that assessments of health and water quality should include measured data and not rely solely on resident perceptions. As differences in education level, resource wealth, and social capital vary from resident to resident, individual perceptions should be considered alongside quantitative data that can support or contrast those perceptions.…”
Section: Methodological Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies either focused on one or the other, with some studies only examining measured water quality using quantitative methodologies, and other studies only discussing perceived water quality using more qualitative methodologies (e.g., Moya 2017). However, Rowles et al (2020a) found that the relationships between perceived and measured water quality suggest that assessments of health and water quality should include measured data and not rely solely on resident perceptions. As differences in education level, resource wealth, and social capital vary from resident to resident, individual perceptions should be considered alongside quantitative data that can support or contrast those perceptions.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Nine of the included studies focused on water quality (Leach et al 1999(Leach et al , 2000Laware & Rifai 2006;Rios & Meyer 2009;Cardenas et al 2010;Travis et al 2010;Balazs et al 2011;Moore et al 2011;Rowles et al 2020b). Four studies examined environmental health (Berry et al 1997;Mier et al 2008;Moya 2017;Rowles et al 2020a), and three studies focused on mental health of water and sanitation insecurity (Garcia et al 2016;Hargrove et al 2018;Pierce et al 2019).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some methods have been devoted to studying the interaction among accident factors, including System eoretic Accident Modeling and Processes (STAMP) [11,12], Functional Resonance Analysis Method (FRAM) [13], "2-4" model [14], Structural Equation Modeling (SEM) [15,16], etc. STAMP, FRAM, and the "2-4" model require finding out the interaction.…”
Section: Introductionmentioning
confidence: 99%